1999
DOI: 10.1093/ajcn/69.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Maternal folate status during extended lactation and the effect of supplemental folic acid

Abstract: Background: Folate requirements during lactation are not well established. Objective:We assessed the effects of dietary and supplemental folate intakes during extended lactation. Design: Lactating women (n = 42) were enrolled in a doubleblind, randomized, longitudinal supplementation trial and received either 0 or 1 mg folic acid/d. At 3 and 6 mo postpartum, maternal folate status was assessed by measuring erythrocyte, plasma, milk, and dietary folate concentrations; plasma homocysteine; and hematologic indexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 34 publications
5
65
1
2
Order By: Relevance
“…As expected, we found a statistically significant inverse relation between tHcy and folate, also found in our preliminary cross-sectional investigation (Ramlau-Hansen et al, 2003) and in agreement with results from the double-blind, randomized, longitudinal supplementation trial by Mackey and Picciano (1999).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, we found a statistically significant inverse relation between tHcy and folate, also found in our preliminary cross-sectional investigation (Ramlau-Hansen et al, 2003) and in agreement with results from the double-blind, randomized, longitudinal supplementation trial by Mackey and Picciano (1999).…”
Section: Discussionsupporting
confidence: 92%
“…Several investigations show an increased risk of suboptimal folate status (Matoth et al, 1965;Donangelo et al, 1989;Lehti, 1989;Ramlau-Hansen et al, 2003;Villalpando et al, 2003) and a reduction in folate stores during the lactation period (Shapiro et al, 1965;Tamura et al, 1980;Butte et al, 1981;Sneed et al, 1981;Smith et al, 1983;Dostalova, 1984;Bruinse et al, 1985;Bates et al, 1986;Salmenpera et al, 1986;Keizer et al, 1995;Mackey and Picciano, 1999) in women with no folic acid supplementation and with a diet insufficient in folate. Others have shown that lactation does not affect the level of folate (Cole et al, 1974;Thomas et al, 1980;Ek, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that lactational performance could be affected because folic acid supplementation can impair folate secretion into milk (Mackey & Picciano, 1999). It also disrupts the normal inverse relationship between dietary folate and plasma homocysteine (Mackey & Picciano, 1999), which may be related to changes in maternal folic acid metabolism (Smith et al 1983).…”
Section: Maternal Dietary Manipulation During Development and Programmentioning
confidence: 99%
“…The requirements for many micronutrients such as vitamin B 12 are higher during pregnancy and lactation owing to transfer to the baby (Allen, 1994;Mackey and Picciano, 1999). A few studies have shown that the vitamin B 12 status of the mother is associated with the content of vitamin B 12 in breast milk (Baker et al, 1962;Black et al, 1994) and with the vitamin B 12 status of the baby (Specker et al, 1988), indicating that the amount of vitamin B 12 released into the breast milk and thereby available to the baby depends on the vitamin B 12 status of the mother.…”
Section: Introductionmentioning
confidence: 99%